2006
DOI: 10.1002/cbic.200600194
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Exocytosis in Chromaffin Cells by Trans‐Insertion of Lysophosphatidylcholine and Arachidonic Acid into the Outer Leaflet of the Cell Membrane

Abstract: Vesicular exocytosis is an important complex process in the communication between cells in organisms. It controls the release of chemical and biochemical messengers stored in an emitting cell. In this report, exocytosis is studied amperometrically (at carbon fiber ultramicroelectrodes) at adrenal chromaffin cells, which release catecholamines after appropriate stimulation, while testing the effects due to trans-insertion of two exogenous compounds (lysophosphatidylcholine (LPC) and arachidonic acid (AA)) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 40 publications
12
84
1
Order By: Relevance
“…They found that LPC facilitates catecholamine release (rate, event frequency, charge released) while AA inhibits the exocytotic processes. They also observed that the detected amount of neurotransmitters in the presence of LPC was larger than under control conditions, while the opposite trend is observed with AA (Amatore et al 2006). …”
Section: Lipid Composition Of the Plasma Membranementioning
confidence: 93%
See 2 more Smart Citations
“…They found that LPC facilitates catecholamine release (rate, event frequency, charge released) while AA inhibits the exocytotic processes. They also observed that the detected amount of neurotransmitters in the presence of LPC was larger than under control conditions, while the opposite trend is observed with AA (Amatore et al 2006). …”
Section: Lipid Composition Of the Plasma Membranementioning
confidence: 93%
“…The most direct evidence that the fraction released can be altered was presented by both the Amatore and Ewing groups who showed that the amount of neurotransmitter released per event can be quickly altered by influencing the lipid composition of the plasma membrane (Amatore et al 2006;Mellander et al 2012;Uchiyama et al 2007). In one case, they found that a shortterm incubation of PC12 cells with the inverted cone shaped lipid lysophosphatidylcholine (LPC) increased the average amount of dopamine released per exocytosis event while incubation with the cone shaped phosphatidylethanolamine (PE) decreased it.…”
Section: Lipid Composition Of the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…These brief incubations were performed immediately before stimulating release [71], with the intention of altering the fusogenic and dissipative properties of the membrane assembly [78][79][80][81][82][83]. The brief incubations ensured that exogenous lipids exclusively trans-inserted in the outer leaflet of the cell membrane [82], with opposite consequences for the large positive curvatures at the fusion pore edges [36,[53][54][55][75][76][77]84,85] due to their shapes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, incubation of isolated chromaffin granules with arachidonic acid (negative intrinsic curvature) promotes fusion (32). Amatore et al recently showed that these lipids could each produce the opposite effect when added to the extracellular media (the noncontact side of the fusing membranes) of chromaffin cells undergoing exocytosis (33). In a similar experiment PC12 cells were incubated with dipalmitoylphosphatidylcholine, a lamellar lipid (close to no intrinsic curvature), resulting in a decrease in the rate of exocytosis (34).…”
Section: Discussionmentioning
confidence: 99%